Using Scopesim to Plan Research With the Extremely Large Telescope - Gardner, Kristen (My University, 2025)
The python package Scopesim was used to simulate observations with the Extremely Large Telescope. The simulations were used to assess potential research objectives for the ELT. Two case studies were conducted with a set of transient observation simulations: a type Ia supernova and a host galaxy were simulated at varying redshifts, and a supernova progenitor in a star cluster was simulated at varying distances. The simulations were used to analyze the point spread function of the ELT in the Ks, J and Y bands. Difference imaging was used to isolate each target PSF. Strehl ratios were higher at longer wavelengths: 0.55 in the Ks band, 0.22 in the J band, and 0.16 in the Y band. The full-width at half-maximum of the PSF in each respective band was 13.5 mas, 6 mas, and 6 mas, when simulating a 1.5 mas pixel scale. For an exposure time of 1h, the detection limit for a point source is in the range of 26 to 28 mag. Signal-to-noise ratio values were higher at shorter wavelengths, and higher when using a larger pixel scale (4 mas). The PSF was closer to its diffraction limit at longer wavelengths.
Keywords: Adaptive Optics, Scopesim, Extremely Large Telescope, MICADO, Difference Imaging, Transient Astronomy, Astronomy Simulation